The Role of Railway Infrastructure Development on the Regional Economic Growth - Dwiatmoko, Hermanto; Supriyatno, Dadang; Mudjanarko, Sri Wiwoho (International Journal of Sustainable Construction Engineering and Technology, 2020)
This paper aims to investigate the impact of railway infrastructure development on the Indonesia national economy. The data used in this study are Gross Regional Domestic Product (GRDP), Railway Assets, Government Budget for Railway, Employee Cost, Consumer Price Index, and Railway Income. The data collected from 10 provinces in Java and Sumatera from 2000 to 2015. Panel data was processed using E-Views 9.0 software. The results of econometric analysis indicate a positive relationship among each variable, development budget, railway assets, railway income and employee cost and Gross Regional Domestic Product which represents the regional and national economy. An increase in railway development budget and railway assets in Java will result in a bigger GRDP compared to Sumatera because there are relatively more railway assets, thereby increasing passenger and freight transportation services. From these analyses can be suggested policy implementation by prioritizing the development of railway infrastructure to increase GRDP. The development of railway infrastructure in the island of Sumatera is expected to further increase GRDP.